Contraceptive counselling of women seeking abortion – a qualitative interview study of health professionals' experiences. (2nd January 2017) - Kilander, Helena; Salomonsson, Birgitta; Thor, Johan; Brynhildsen, Jan; Alehagen, Siw
Abstract: Objectives: A substantial proportion of women who undergo an abortion continue afterwards without switching to more effective contraceptive use. Many subsequently have repeat unintended pregnancies. This study, therefore, aimed to identify and describe health professionalś experiences of providing contraceptive counselling to women seeking an abortion. Methods: We interviewed 21 health professionals (HPs), involved in contraceptive counselling of women seeking abortion at three differently sized hospitals in Sweden. The interviews were recorded and transcribed verbatim and analysed using conventional qualitative content analysis. Results: Three clusters were identified: 'Complex counselling', 'Elements of counselling' and 'Finding a method'. HPs often experienced consultations including contraceptive counselling at the time of an abortion as complex, covering both pregnancy termination and contraceptive counselling. Women with vulnerabilities placed even greater demands on the HPs providing counselling. The HPs varied in their approaches when providing contraceptive counselling but also in their knowledge about certain contraception methods. HPs described challenges in finding out if women had found an effective method and in the practicalities of arranging intrauterine device (IUD) insertion post-abortion, when a woman asked for this method. Conclusions : HPs found it challenging to provide contraceptive counselling at the time of an abortion and to arrange access to IUDs post-abortion. There is a need to improve their counselling, their skills and their knowledge to prevent repeat unintended pregnancies.